ANALISIS PENGELOLAAN BIAYA BAHAN BAKU PADA PT PERKEBUNAN NUSANTARA (PTPN) XIV (STUDI KASUS PABRIK GULA ARASOE) - Salam Galib, Nur Azizah; Idrus, Muhammad; Syafridayani, Syafridayani (LPPM Universitas Muhammadiyah Mamuju, 2024)
Research Objectives 1) To determine the economical quantity of sugar cane raw material supplies in daily granulated sugar production during the milling season at the Bone Arasoe Sugar Factory. 2) To determine the efficiency of raw material inventory costs with production costs incurred by the Bone Arasoe Sugar Factory. 3) To find out how to control the supply of sugarcane raw materials so that the intensity of sugarcane raw materials for the production process can be evenly distributed during the milling season. Research results 1) Production quantity per day according to calculations using the EPQ method shows a greater value when compared with production calculations according to company policy. Daily production quantities according to the EPO method during 2017 - 2021 are respectively 2,655.50 tons, 2,536.19 tons: 2,641.02 tons,2,792.69 tons and 2,917.70 tons. 2) The total production costs for making granulated sugar per day according to calculations using the EPQ method are smaller than the total production costs carried out by the company. 3) To schedule sugarcane raw materials at the Sugar Factory Bone Arasoe So that the intensity of sugarcane raw materials for the production process can be evenly distributed during the milling season, planting and cutting periods can be scheduled based on rainfall data.